Quality of Higher Education: A Bibliometric Review Study - Brika, Said Khalfa M.; Algamdi, Abdelmageed; Chergui, Khalil; Musa, Adam A.; Zouaghi, Rabia (Frontiers in Education, 2021)
For more than three decades, higher education has attracted growing interest from scholars, students, and academic institutions worldwide. This paper aims to analyze the literature review of quality of higher education, using the bibliometric analysis adapted from VOSviewer software to examine the data of 500 studies published in the Web of Science from 2000 to 2018 related to this topic. The results were presented and discussed with the following approaches: keywords, authors, references (research papers), research work, countries, and research institutions. The study found that bibliometric analysis is fundamental in detailing the theoretical literature and developing an integrated theoretical framework on quality of higher education. This review provides reference points for entry into this interdisciplinary field.